Anemochore Seeds Harbor Distinct Fungal and Bacterial Abundance, Composition, and Functional Profiles - Dong Liu; Jie Cai; Huajie He; Shimei Yang; Caspar C. C. Chater; Fuqiang Yu (Journal of Fungi, 2022)
Many plants adapted to harsh environments have evolved low seed mass (‘light seeds’) with specific dispersal strategies, primarily either by wind (anemochory) or water (hydrochory). However, the role of their seed microbiota in their survival, and their seed microbial abundance and structure, remain insufficiently studied. Herein, we studied the light seed microbiome of eight anemochores and two hydrochores (as controls) collected from four provinces in China, using qPCR and metagenomic sequencing targeting both bacteria and fungi. Substantial variations were found for seed endophytic fungi (9.9 × 1010~7.3 × 102 gene copy numbers per seed) and bacteria (1.7 × 1010~8.0 × 106). Seed microbial diversity and structure were mainly driven by the plant genotype (species), with weak influences from their host plant classification level or dispersal mode. Seed microbial composition differences were clear at the microbial phylum level, with dominant proportions (~75%) for Proteobacteria and Ascomycota. The light seeds studied harbored unique microbial signatures, sharing only two Halomonas amplicon sequence variants (ASVs) and two fungal ASVs affiliated to Alternaria and Cladosporium. A genome-level functional profile analysis revealed that seed bacterial microbiota were enriched in amino acid, nucleoside, and nucleotide biosynthesis, while in fungal communities the generation of precursor metabolites and respiration were more highly represented. Together, these novel insights provide a deeper understanding of highly diversified plant-specific light seed microbiota and ecological strategies for plants in harsh environments.